The Influence of Education Expenditures and Health Expenditures on Poverty Through HDI (A Case Study: 35 Regencies and Cities in Central Java in the 2018-2023 Period) - Maesur Sindi, Amalia; Suman, Agus (Journal of Development Economic and Social Studies, 2026)
Poverty reduction remains a critical challenge in regional development, particularly in en-suring that public spending effectively translates into improved welfare outcomes. This study aims to examine the effects of education and health expenditures on poverty, with the Human Development Index (HDI) as a mediating variable. Employing a quantitative approach, the research utilizes panel data from 35 regencies/cities in Central Java Province over the period 2018–2023 and applies path analysis using a Fixed Effect Model (FEM). The results indicate that education and health expenditures do not have a significant direct impact on poverty levels. In contrast, HDI is found to have a significant negative effect on poverty, suggesting that improvements in human development contribute to poverty re-duction. Furthermore, mediation analysis reveals that HDI does not mediate the relation-ship between education expenditure and poverty, but it significantly mediates the effect of health expenditure on poverty. These findings imply that the effectiveness of government spending in reducing poverty depends not merely on budget allocation, but on its capacity to enhance human development outcomes.